New strategies in prostate cancer: prostate-specific membrane antigen (PSMA) ligands for diagnosis and therapy - Haberkorn, Uwe; Eder, Matthias; Kopka, Klaus; Babich, John W.; Eisenhut, Michael (Clinical cancer research, 2016)
Key issues for prostate cancer patients are the detection of recurrent disease and the treatment of metastasized cancer. Early detection is a major challenge for all conventional imaging modalities. Furthermore, therapy of patients with hormone-resistant tumor lesions presents a major clinical challenge. Because the prostate-specific membrane antigen (PSMA) is frequently overexpressed in prostate cancer, several PSMA-targeting molecules are under development to detect and treat metastatic castration-resistant prostate cancer (mCRPC). mCRPC represents a situation where cure is no longer achievable and novel therapeutic approaches for palliation and increase of survival are needed. In this article, we discuss the recent development for noninvasive detection of recurrent disease and therapy of mCRPC with corresponding PSMA-targeted radioligands. Clin Cancer Res; 22(1); 9-15. ©2016 AACR.